Copycat Firesetting: Bridging Two Research Areas. (December 2013) - Doley, Rebekah; Ferguson, Claire; Surette, Ray
Deliberate firesetting costs our community in destruction to property and lives. Public concern heightens when similar fires occur in a series, raising the specter of copycat firesetting. Difficulties associated with researching copycat crimes in general mean that not a lot is known about copycat firesetting. As an initial step toward filling this research gap, we explore connections between research on copycat crime and research into deliberate firesetting. The intention is to extract salient features from what is known about the phenomena of deliberate firesetting and copycat crime, map them together, and point out shared and unique characteristics. It is argued that a "copycat firesetter" is likely to exist as a distinct subgroup and potentially requiring targeted interventions.